Robust rotordynamics - Rix, Andrew Iain James (2016)
Vibration generated from main rotor unbalance has a major impact on the aerospace gas turbine industry. A combination of logistical and technological drivers differentiate aerospace gas turbines and their derivatives from other types of gas turbines with respect to the approach for managing vibration, leading to a bespoke approach for the design, build, and balancing. The key drivers are: limited accessibility to rotors within the engine, the requirement for exchangeable modules (sub-assemblies) of major parts of the rotor without rebalancing, the use of only low-speed balancing on pseudo-rigid rotors with bladed assemblies, very low vibration limits leading to very tight balancing limits, extreme weight limits for design solutions, and the need for highly accurate, repeatable, and stable rotor joints.